Determinant of Social Norms - Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2022)
It is now abundantly clear that social norms channel behavior and impact economic development. This insight leads to the question: How do social norms evolve? This survey examines research that relies on geography to explain the development of social norms, and suggests that religion and family organization are potential mediators. It turns out that many social norms are either directly or indirectly determined by geography and can, hence, be considered largely time invariant. Given that successful economic development presupposes the congruence between formal institutions and social norms, this insight is highly relevant for all policy interventions designed to facilitate economic development.
Keywords: A13; D90; K00; O10; Z10; 330; social norms; internal institutions; informal institutions; Institutional Economics; geography; religion; family